2023
DOI: 10.1001/jamanetworkopen.2023.6693
|View full text |Cite
|
Sign up to set email alerts
|

Mortality After Postcolonoscopy Colorectal Cancer in the Veterans Affairs Health Care System

Abstract: ImportancePostcolonoscopy colorectal cancer (PCCRC) refers to colorectal cancer (CRC) diagnosed after a colonoscopy in which no cancer was found and is reflective of colonoscopy quality at the individual and system levels. Colonoscopy is widely performed in the Veterans Affairs (VA) health care system, but the prevalence of PCCRC and its associated mortality are unknown.ObjectiveTo examine PCCRC prevalence and its all-cause mortality (ACM) and CRC-specific mortality (CSM) within the VA health care system.Desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…In summary, Kahi et al 5 demonstrate that colonoscopy quality in the VA system is comparable to that of other health settings using PCCRC-3y as a benchmark, and that patients classified with PCCRC-3y have similar mortality event rates to those with CRC detected by colonoscopy, but lower mortality compared to those without colonoscopy. Further research to evaluate the influence of race and ethnicity, differential care settings, and other established quality metrics on PCCRC-3y will be important.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…In summary, Kahi et al 5 demonstrate that colonoscopy quality in the VA system is comparable to that of other health settings using PCCRC-3y as a benchmark, and that patients classified with PCCRC-3y have similar mortality event rates to those with CRC detected by colonoscopy, but lower mortality compared to those without colonoscopy. Further research to evaluate the influence of race and ethnicity, differential care settings, and other established quality metrics on PCCRC-3y will be important.…”
mentioning
confidence: 92%
“…In JAMA Network Open , Kahi and colleagues 5 evaluated the prevalence and mortality of patients with PCCRC-3y receiving care in the Veterans Health Administration (VA). They performed a retrospective cohort study using VA-Medicare administrative data that identified a total of 29 877 incident cases of CRC between 2003 and 2013, of which 1785 (6.0%) were classified as PCCRC-3y.…”
mentioning
confidence: 99%